'Visiting time: A tale of two prisons': A practitioner perspective. (March 2017) - Alston-Smith, Summer
Marie Hutton's 2016 article, 'Visiting Time: A Tale of Two Prisons', compares the visiting experience across two male prison establishments and examines whether Article 8 of the European Convention on Human Rights – the right to 'private and family life' – was respected in the visitation process. This article seeks to compare the conclusions of this relatively small sample base to the wider prison system including female and young offender establishments, lending a national and political context.